2015
DOI: 10.1371/journal.pone.0142569
|View full text |Cite
|
Sign up to set email alerts
|

Effective Suppression of Methane Emission by 2-Bromoethanesulfonate during Rice Cultivation

Abstract: 2-bromoethanesulfonate (BES) is a structural analogue of coenzyme M (Co-M) and potent inhibitor of methanogenesis. Several studies confirmed, BES can inhibit CH4 prodcution in rice soil, but the suppressing effectiveness of BES application on CH4 emission under rice cultivation has not been studied. In this pot experiment, different levels of BES (0, 20, 40 and 80 mg kg-1) were applied to study its effect on CH4 emission and plant growth during rice cultivation. Application of BES effectively suppressed CH4 em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…The inhibitor BES used in the treatments –A and –AFP is a structural analog of coenzyme M (Co-M) and directly competes with Co-M for the methyl group (Guo et al, 2008 ). By this way, BES inhibits the activity of the methyl-Co-M reductase in archaea and thus the CH 4 production (Waghmode et al, 2015 ). In the present study, no CH 4 emission was detected in the treatments with BES and correspondingly the abundance of mcrA gene coding for alpha subunit of methyl-Co-M reductase enzyme was reduced by up to 96% (–A) and 98% (–AFP).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitor BES used in the treatments –A and –AFP is a structural analog of coenzyme M (Co-M) and directly competes with Co-M for the methyl group (Guo et al, 2008 ). By this way, BES inhibits the activity of the methyl-Co-M reductase in archaea and thus the CH 4 production (Waghmode et al, 2015 ). In the present study, no CH 4 emission was detected in the treatments with BES and correspondingly the abundance of mcrA gene coding for alpha subunit of methyl-Co-M reductase enzyme was reduced by up to 96% (–A) and 98% (–AFP).…”
Section: Discussionmentioning
confidence: 99%
“…Eng., 45(9), [388][389][390][391][392][393][394][395][396][397][398][399]2023 https://doi.org/10.4491/KSEE.2023. 45 32,33) 에 따라 조사하였다. 감자는 초장(cm), 괴경수(개수), 괴경무게(g), 수 확량(t/ha)을 조사하고, 배추는 초장(cm), 엽폭(cm), 엽수(개 수), 구폭(cm), 구고(cm), SPAD(지수), 결구 유무(%), 무게(g), 수확량(t/ha)을 조사하였다.…”
Section: 이연진ㆍ임은채ㆍ홍성창ㆍ박성직unclassified
“…The major anaerobic sites of methanogenesis are paddy fields, ruminants, natural wetlands, and sediment, 4) with paddy fields contributing about 5-19% of total global methane emissions. 5) According to the National Greenhouse Gas Inventory Report of Japan 2021, 6) total methane emission rates in Japan (28.5 Mt CO 2 eq. in 2019) have decreased by 35.2% since 1990.…”
Section: Introductionmentioning
confidence: 99%
“…7) A pot experiment with 2-bromoethanesulfonate (BES) 8,9) showed that application at 80 mg/kg of BES caused a 49% reduction in methane emission without affecting plant growth and productivity during rice cultivation. 5) Many studies on methanogenic inhibitors have been conducted to mitigate methane emissions from ruminants, with the most successful compounds tested in vivo including BES, bromochloromethane, chloroform, and cyclodextrin. 10) In addition, amichloral, trichloroacetamide, trichloroethyl adipate, 9,10-anthraquinone, 3-bromopropanesulfonate, lumazine, propynoic acid, and ethyl 2-butynoate have been studied for their effects on methane production.…”
Section: Introductionmentioning
confidence: 99%